Pengaruh Jumlah Blade, Kemiringan Sudut dan Jarak Pengaduk dari Dasar Pada Proses Koagulasi Flokulasi dalam Menurunkan Parameter TSS dan Kekeruhan - Dzaky, Muhammad Luqman; Tuhu Agung Rachmanto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The quality of river water is influenced by the levels of Total Suspended Solids (TSS) and turbidity, which serve as indicators of environmental pollution. An effective method to reduce these parameters is the coagulation-flocculation process. The effectiveness of this process depends on physicochemical and hydrodynamic factors, including impeller design. However, hydrodynamic aspects such as the number of blades, blade angle, and distance of the impeller from the bottom are rarely considered in detail in previous studies. Therefore, the objective of this study is to analyze the optimal impeller design to improve TSS and turbidity removal efficiency. This study examines variations in the number of blades (2, 4, and 6), blade angles (0°, 30°, 45°, and 60°), and impeller distance from the bottom (3 cm, 4 cm, and 5 cm). The results indicate that the optimum impeller design for TSS and turbidity reduction is 6 blades, 0° blade angle, and 5 cm impeller distance from the bottom. Under these conditions, TSS removal reached 93.5%, while turbidity removal reached 98.2%. These results demonstrate that proper impeller design can significantly improve the efficiency of the coagulation-flocculation process.